Towards Green Tourism Development: Customers’ Perception of Using Plastic Products in the 5-star Hotels in Ho Chi Minh City - Van Hoang Nguyen; Quang Dai Tuyen; Nguyen Thi Huynh Mai; Le Hong Hanh; Nguyen Ngoc Ha (ASEAN Journal on Hospitality and Tourism, 2022)
In recent years, green tourism has become a development trend, attracting the attention of the community, tourism businesses and tourists in many countries around the world. However, the approach of green tourism development in Vietnam is still limited in terms of scale and participants. This article examines the situation of using plastic products and the plastic waste treatment in the 5-star hotels in Ho Chi Minh City. Specifically, this study aims to explore the perception of customers of the use of plastic products. By doing so, the study contributes to clarifying the current situation of green tourism development in the hotel sector in the study area. The authors used the research methods of questionnaire, semi-structured interview and non-participant observation to conduct this study. Research results show that although the use of plastic products in hotels is still high, the plastic waste treatment is not thorough because of high treatment costs. But, the hotels tend to change policy on the treatment of plastic waste in an environmentally friendly manner. Besides, customers’ perception of plastic products is completely positive related to their attitudes when using, the willingness to pay and the desire to access more environmentally friendly services and products in the hotel sector. Based on the results, the article also discusses and suggests implications and approaches to developing products and services in hotels towards the development of green tourism and sustainable tourism in the future.